The Academic Performance of Students in Class XI at SMA Negeri 1 Suak Tapeh, Suak Tapeh District, Banyuasin Regency : The Impact of Smartphone Use - Sherly Desliyanah; Sarwono Hadi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research discusses the impact of smartphone use on the academic performance of 11th-grade students at SMAN 1 Suak Tapeh. The development of technology, especially the use of smartphones, has a significant impact on people's lives, including in the field of education. The use of smartphones can have both positive and negative effects on students' academic performance. The research adopts a qualitative approach with a descriptive method. Primary data were collected through interviews, observations, and documentation, while secondary data were obtained from relevant documents or archives. The findings reveal that smartphones have positive effects, such as facilitating access to learning materials, enhancing creativity, and broadening knowledge. However, uncontrolled smartphone use can lead to negative effects, such as addiction, sleep disturbances, decreased concentration, and diminished quality of social interactions. This study is expected to provide insights into the benefits and risks of smartphone use in supporting students' learning processes and offer recommendations for schools in designing policies related to smartphone use among students.